Circular economy from waste to resource: 7Rs innovative practices in Amsterdam. Technologie "die nog in de kinderschoenen staan” - Arisi, Barbara Maisonnave (ILUMINURAS, 2020)
Abstract: Amsterdam city is proud of being a worldwide center for innovation, in 2016 it was named by the European Commission as the “European Capital of Innovation” (Iamsterdam 2020). This paper analyses seven innovative practices that deal with solid residue in The Netherlands, experiences that try to move towards a “circular bioeconomy” (Hetemäki et alli 2017). I classify the innovation cases I researched in reference to the 7Rs: 1) Rethink, 2) Reduce/Refuse, 3) Reuse/Rehome/Repurpose, 4) Recycle, 5) Recreate, 6) Repair and 7) Rot. My main objective is to bring ideas and images to inspire practitioners and academic fellows to experiment or to adapt from these innovation experiences. I will try to bring some of the new debates concerning the concepts of “circular economy”, “circular society” and the more contemporary one that is “circular bioeconomy” (Hetëmaki et alli. 2017). Finally, to end, I address the role of utopia and imagination as important forces that animate bio/social innovation to reproduce life. Keywords: circular economy; circular bio economy; innovation; solid residue management; Amsterdam. ECONOMIA CIRCULAR - DOS RESÍDUOS AOS RECURSOS: 7RS PRÁTICAS INOVADORAS EM AMSTERDÃ. TECHNOLOGIE "DIE NOG IN DE KINDERSCHOENEN STAAN". Resumo: A cidade de Amsterdã orgulha-se de ser um centro mundial de inovação; em 2016 foi nomeada pela Comissão Europeia como a "Capital Europeia da Inovação" (Iamsterdam 2020). Este artigo analisa sete práticas inovadoras que lidam com resíduos sólidos nos Países Baixos, experiências que tentam avançar para uma “economia circular". Classifico os casos de inovação que investiguei em referência aos 7Rs: 1) Repensar, 2) Reduzir/Recusar, 3) Reutilizar/Recuperar/Redirecionar, 4) Reciclar, 5) Recriar, 6) Reparar e 7) CompostaR. O meu principal objetivo é apresentar ideias e imagens para inspirar profissionais e acadêmicos a experimentar ou a adaptar projetos a partir destas experiências de inovação. Abordo também alguns dos novos debates sobre os conceitos de "economia circular", "sociedade circular" e "bioeconomia circular". Finalmente, e para terminar, trato do papel da utopia e da imaginação como forças importantes para animar a inovação bio/social e para reproduzir a vida. Palavras-chave: economia circular. bioeconomia circular. Inovação. gestão de resíduos sólidos. Amsterdã